KONSEP DAN IMPLEMENTASI KEPEMIMPINAN ISLAMI DI UIN MALIKI MALANG - Diana, Ilfi Nur (ULUL ALBAB Jurnal Studi Islam, 2011)
Moslem intellectuals, inter alia : al Farabi, al Mawardi, al Ghazali, Ibnu Taimiyah, Inbu Khaldun, and Jamaludin al Afghani have factually addressed concepts of Islamic leadership since the classical era. Unfortunately, only a few Moslem researchers further study them and they are not yet further developed optimally. Accordingly, it is deemed necessary to further study about Islamic leadership by identifying the parameters advocated by Moslem leaders. The purpose of this study is to explore of Islamic leadershipÂ  at Maliki Islamic State University (UIN) Malang. This research used 144 employees as samples. To test Islamic leadership at this unversity, factor analysis is used. The results of factor analysis showed that of the 30 proposed questions, 5 of them were excluded, namely :sincerity (not expecting material rewards), tenacity, friendliness, firmness to give sanctions to indiscipline subordinates and deliberation (openness to accept inputs from subordinates), and the extracted factors were 8 Accumulatively, Islamic leadership was justified by 68.8%. p. It was conclusive that the research contributed to Islamic leadership parameters adopted from the thoughts of classical through modern Moslem intelectuals.